REMODELING BENSON’S LEARNER AUTONOMY FRAMEWORK: A LIBRARY-BASED STUDY - Yulina, Christina Atika (Universitas Suryakancana, 2025)
Early theorists like Holec (1981) defined autonomy as the ability to take charge of one's own learning, while later scholars such as Little (1991) expanded this concept by adding essential psychological dimension, which covers two key dimensions of autonomy: control over learning management and control over cognitive process which is underlied by psychology of learning. Benson (2013) then added situational aspect of control over learning content and formulated this concept into a three-dimensional model in which learner control can be exercised: learning management (underlied by learning behavior), cognitive processes (underlied by psychology of learning) and learning content (underlied by learning situation). Despite these developments, the visual and conceptual representations of autonomy appear fragmented and may not sufficiently illustrate the interconnections among its dimensions, lacking a visual explanation of how they dynamically interact in autonomous learning and leaving room for a clearer, more integrated framework that helps educators and learners alike understand the interdependence of autonomy's dimensions. This study, conducted as a library-based analysis, critically reviews existing theoretical models and proposes a remodeled framework to address these conceptual gaps. The primary purpose of this paper is to remodel Benson’s framework of control in learning autonomy, without attempting to integrate other theoretical perspectives such as Self-Regulated Learning (SRL) or Self-Directed Learning, nor does it propose new theoretical dimensions beyond Benson’s three control areas.